HISTOPATHOLOGICAL AND IMMUNOHISTOCHEMICAL FINDINGS OF PLACENTAS IN PREGNANT PATIENTS WITH SARS-COV-2 (International Seven Journal of Health Research, 2025)
Blackground: Due to the pandemic, different diagnostic studies are being carried out throughout the world to identify the virus in the first place, determine the accompanying symptoms and complications that can alter normal hemostasis in patients, and in our environment it is no different since pregnant women per se have a diminished immune system.Objective: determine the histopathological and Inmunohistochemical finding of the placentas in pregnant patients with Covid-19.Methods: a descriptive study of 30 patients was carried out at the Leonardo Martinez Valenzuela Hospital, San Pedro Sula, Honduras during three months of 2021, where a histopathological and inmunohistochemical study of the placentas of pregnant patients with Covi-19 was carrie out.Results: histopathological studies of the placentas found congestive, infectious and inflammatory , infectious, and congestive changes, immunohistochemical studies with RT-PCR on each of the placenta samples without finding evidence of vertical transmission.Discusion: the histopathological changes produced in the placentas by covid infection can determine the degree of affectation of the developing fetus.